Medieval matching markets - Lars Börner; Daniel Quint (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2010)
This paper studies the market microstructure of pre-industrial Europe. In particular we investigate the institution of the broker in markets and fairs, and develop a unique data set of approximately 1100 sets of brokerage rules in 42 merchant towns in Central and Western Europe from the late 13th to the end of the 17th century. We show that towns implemented brokerage as an efficient matchmaking institution in a two-sided market problem. Furthermore, towns differentiated seller-friendly from buyer-friendlier matching mechanisms. We show that the decision to implement matchmaking mechanisms, and whether these mechanisms would be buyer- or seller friendly, depends on the products in question and the stated policy goals of the town, as well as time and geographic variables.
Keywords: D4; N23; 330; preindustrial markets; market microstructure; efficient matching; Marktveranstaltung; Makler; Markteffizienz; Wirtschaftsgeschichte; Mittelalter; Europa